2023
DOI: 10.1021/acsnano.3c01005
|View full text |Cite
|
Sign up to set email alerts
|

Foodborne Carbon Dot Exposure Induces Insulin Resistance through Gut Microbiota Dysbiosis and Damaged Intestinal Mucus Layer

Abstract: Foodborne carbon dots (CDs), an emerging food nanocontaminant, are an increasing risk factor for metabolic toxicity in mammals. Here, we report that chronic CD exposure induced glucose metabolism disorders via disruption of the gut−liver axis in mice. 16s rRNA analysis demonstrated that CD exposure decreased the abundance of beneficial bacteria (Bacteroides, Coprococcus, and S24-7) and increased the abundance of harmful bacteria (Proteobacteria, Oscillospira, Desulfovibrionaceae, and Ruminococcaceae), as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Compared with the control and TiO 2 nanoparticle groups, the proportion of Firmicutes and Bacteroidetes increased in the whey protein and whey protein-coated nanoparticle groups, especially in the whey protein group. Previous studies have reported that a decrease in the ratio of Firmicutes to Bacteroidetes (F/B) is associated with a decrease in energy intake, so the addition of whey protein may increase energy intake in the body. , Previous studies have also reported that an increased F/B ratio is associated with metabolic syndrome, which is a sign of gut microbiota associated with diet-induced obesity, hyperglycemia, and other metabolic disorders …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Compared with the control and TiO 2 nanoparticle groups, the proportion of Firmicutes and Bacteroidetes increased in the whey protein and whey protein-coated nanoparticle groups, especially in the whey protein group. Previous studies have reported that a decrease in the ratio of Firmicutes to Bacteroidetes (F/B) is associated with a decrease in energy intake, so the addition of whey protein may increase energy intake in the body. , Previous studies have also reported that an increased F/B ratio is associated with metabolic syndrome, which is a sign of gut microbiota associated with diet-induced obesity, hyperglycemia, and other metabolic disorders …”
Section: Resultsmentioning
confidence: 97%
“…Compared to the control group, the TiO 2 nanoparticles increased the proportion of harmful bacteria ( Klebsiella ) and decreased the proportion of beneficial bacteria ( Collinsella ). In contrast, the free and adsorbed whey protein had the opposite effect, suggesting that whey protein could regulate the composition of the gut microbiota, increasing the number of beneficial bacteria and reducing the number of harmful bacteria . In addition, compared to the uncoated nanoparticle group, the proportion of Bacteroides in the coated nanoparticle group increased after fermentation for 24 h. Studies have shown that Bacteroides mainly participate in the degradation of carbohydrates, produce short-chain fatty acids, provide nutrients and energy for the body, and play an important role in improving the metabolism and immune disorders of obese individuals. , It should be noted that it is usually too simplistic to divide gut bacteria into “beneficial” and “harmful” groups, as this depends on the context, such as the health of the person.…”
Section: Resultsmentioning
confidence: 97%
“…Mice were administered a mixture of antibiotics (vancomycin [0.5 g/L], neomycin sulfate [0.5 g/L], metronidazole [1 g/L], and ampicillin [1 g/L]; Sigma-Aldrich) in their drinking water for 5 consecutive days prior to FMT. Fecal transplant was conducted according to established protocols [40][41][42]. Brie y, 8-weekold male donor mice were fed either HFD or HFD + PS, while recipient mice were fed microbiota derived from either HFD or HFD + PS.…”
Section: Fecal Microbiota Transplantation (Fmt)mentioning
confidence: 99%
“…Furthermore, nano TiO 2 additive in food worsens the effects of HFDs on the gut–liver axis and related metabolic diseases by damaging the intestinal mucus layer and causing gut microbiota dysbiosis . Since foodborne CDs also have a small size and can easily enter cells, they may also adversely affect intestinal function and hepatic glucose metabolism in individuals susceptible to metabolic diseases. , Therefore, exploring the effects of food-borne CDs and CDs combined with an HFD on the gut microbiota and gut–liver axis may alert the public to the potential harm of foodborne CD intake and provide theoretical guidance for the treatment of related diseases.…”
Section: Introductionmentioning
confidence: 99%